Protecting a Dalmatian Town: Security Measures in Venetian Split (1480-1550) - Sadovski, Lena (Reti Medievali Rivista, 2023)
Following Niall Ferguson’s assertion that “a catastrophe lays bare the societies and states that it strikes”, this article studies the society of the Dalmatian town of Split through the lens of the various threats it was exposed to around the year 1500, as well as the precautionary measures taken in their anticipation. Based on broad archival evidence, four areas are studied: the military threat posed chiefly by the Ottomans, emigration and depopulation, epidemics, and civil discontent. The study of these measures, ranging from appeasing Ottoman officials to burning infected people’s property, offers new insights into the structures of a society between Venetian rule and Ottoman menace in the Renaissance period.